2021
DOI: 10.3126/ijosh.v11i1.33495
|View full text |Cite
|
Sign up to set email alerts
|

Occupational health hazards and use of personal protective equipment among auto mechanics in Kathmandu Metropolitan City, Nepal

Abstract: Introduction: Auto mechanics are workers who repair and overhaul cars and other automotive vehicles, or their systems and parts. The main objective of the study was to assess knowledge of occupational hazards and the use of safety measures among automobile repair artisans in Kathmandu Metropolitan City. Methods: A cross-sectional study was carried among 400 auto mechanics working garages in Kathmandu Metropolitan City. The data collection was done from May 15th to Jun 13th, 2019. Results: Among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
2
0
0
Order By: Relevance
“…This is comparable to 44.6 years reported by Saliu et al [27] in a similar study from Nigeria. The mean age of the study participants was lower than 28.6 years reported in a study done in Nepal [28]. All the participants in this study were males which is similar to report of study by Ozomata et al [29].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This is comparable to 44.6 years reported by Saliu et al [27] in a similar study from Nigeria. The mean age of the study participants was lower than 28.6 years reported in a study done in Nepal [28]. All the participants in this study were males which is similar to report of study by Ozomata et al [29].…”
Section: Discussionsupporting
confidence: 86%
“…The proportion of automobile mechanics that regularly used overall protective coat or wear while working was 50%. This is comparable to 49.3%% reported in Nepal [ 28 ], but higher than 40% reported by Ozomata et al [ 29 ] in a previous Nigerian study and 27% reported among vehicle repair artisans in a study done in Ghana [ 30 ]. Majority of the automobile mechanics in this study sucked petrol directly with their mouth and frequently used petrol to wash their hands to remove oil residue when repairing vehicles.…”
Section: Discussionsupporting
confidence: 74%